FDG-PET/CT during concomitant chemo radiotherapy for esophageal cancer: Reducing target volumes to deliver higher radiotherapy doses. (June 2015) - Nkhali, Lamyaa; Thureau, Sébastien; Edet-Sanson, Agathe; Doyeux, Kaya; Benyoucef, Ahmed; Gardin, Isabelle; Michel, Pierre; Vera, Pierre; Dubray, Bernard
Abstract Background. A planning study investigated whether reduced target volumes defined on FDG-PET/CT during radiotherapy allow total dose escalation without compromising normal tissue tolerance in patients with esophageal cancer. Material and methods. Ten patients with esophageal squamous cell carcinoma (SCC), candidate to curative-intent concomitant chemo-radiotherapy (CRT), had FDG-PET/CT performed in treatment position, before and during (Day 21) radiotherapy (RT). Four planning scenarios were investigated: 1) 50 Gy total dose with target volumes defined on pre-RT FDG-PET/CT; 2) 50 Gy with boost target volume defined on FDG-PET/CT during RT; 3) 66 Gy with target volumes from pre-RT FDG-PET/CT; and 4) 66 Gy with boost target volume from during-RT FDG-PET/CT. Results. The median metabolic target volume decreased from 12.9 cm3 (minimum 3.7–maximum 44.8) to 5.0 cm3 (1.7–13.5) (p = 0.01) between pre- and during-RCT FDG-PET/CT. The median PTV66 was smaller on during-RT than on baseline FDG-PET/CT [108 cm3 (62.5–194) vs. 156 cm3 (68.8–251), p = 0.02]. When total dose was set to 50 Gy, planning on during-RT FDG-PET/CT was associated with a marginal reduction in normal tissues irradiation. When total dose was increased to 66 Gy, planning on during-RT PET yielded significantly lower doses to the spinal cord [Dmax = 44.1Gy (40.8–44.9) vs. 44.7Gy (41.5–45.0), p = 0.007] and reduced lung exposure [V20Gy = 23.2% (17.3–27) vs. 26.8% (19.7–30.2), p = 0.006]. Conclusion. This planning study suggests that adaptive RT based on target volume reduction assessed on FDG-PET/CT during treatment could facilitate dose escalation up to 66 Gy in patients with esophageal SCC.